2022
DOI: 10.14503/thij-21-7607
|View full text |Cite
|
Sign up to set email alerts
|

Can Right Ventricular Branch Bypass Alleviate Right Ventricular Dysfunction?

Abstract: Background Right ventricle (RV) dysfunction after a coronary artery bypass grafting procedure is a challenge that adversely affects RV filling pressure and contraction. This study sought to determine whether additional bypass of an RV branch would lessen RV dysfunction. Methods Patients with severe right coronary artery (RCA) stenosis were divided into 2 groups. Group 1 patients (n = 50) had a single distal bypass on the RCA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Complete revascularization of extensive RCA disease by bypassing marginal branches, with sequential or separate grafts, has been studied by Turkish groups. 2 , 3 , 4 In these studies, addressing RV free wall ischemia was shown to prevent RV dysfunction and perioperative ischemic events after CABG, especially in patients with left ventricular dysfunction. In the early postoperative period, myocardial protection is commonly blamed for RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Complete revascularization of extensive RCA disease by bypassing marginal branches, with sequential or separate grafts, has been studied by Turkish groups. 2 , 3 , 4 In these studies, addressing RV free wall ischemia was shown to prevent RV dysfunction and perioperative ischemic events after CABG, especially in patients with left ventricular dysfunction. In the early postoperative period, myocardial protection is commonly blamed for RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple surgical groups from Turkey have adopted the concept of RV-free wall revascularization and studied the impact on clinical outcomes [8][9][10]. In a prospective Coronary Artery Bypass Surgery -New Insights randomized study, Güney and Eren compared complete RV revascularization with multiple bypasses to RCA branches (n = 32 patients) to a single conventional bypass to RCA (n = 32 patients) [9].…”
Section: Rv-free Wall Revascularizationmentioning
confidence: 99%
“…In another study of 35 patients with diffuse atherosclerotic disease of the RCA who underwent CABG; RV diastolic function by echocardiography improved in 20 patients with sequential bypass to RCA compared to 15 patients with single bypass to RCA [10]. In another comparative analysis conducted by Sahin et al, 100 patients with multi-segments disease of the RCA underwent off-pump CABG, in which 50 patients had single bypass to distal RCA and 50 patients had additional bypass to marginal branch of RCA [8]. Patients who had additional bypass to the RV branch experienced faster recovery of RV function, less inotropic support, and shorter hospitalization than the group with single distal RCA bypass.…”
Section: Rv-free Wall Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation